A Rational Choice Analysis in Offering The Spirit of The Northern Buddhism - Khang Tan Nguyen; Junardi Harahap; Budi Rajab (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Offering the spirits in the ritual system of Northern Buddhism is a ritual performed daily for monks and an opportunity for Buddhists to participate in many different purposes. In it, there is an exchange between gain and loss while performing the ritual of offering the spirit. It could be said that based on the concepts and beliefs about ghosts and demons in Mong Son thi thuc - one of the important rites in the customs of Northern Buddhists - these rituals give us a deeper insight into the act of worshiping the souls. This research investigates the rational choice of Northern Buddhists in Ho Chi Minh City-based on Rational Choice Theory. Qualitative research methods such as fieldwork, in-depth interviews, qualitative analysis, and quantitative research by questionnaires have shown that there is rationality in the choice of worship the souls according to Mong Son thi thuc of Northern Buddhists among believers. In other words, there seems to be a desire to receive one or more benefits from this spirit offering. Rational Choice Theory has shown its applicability in the study of rituals, religions in particular, and in the research of the humanities and social sciences in general, which has received little attention in the past.